Lack of HPV in pterygium with no evidence of autoinoculation and the role of cytokines in pterygium with dry eye - Lita Uthaithammarat (Nature Portfolio, 2021)
Abstract This study evaluated human papillomavirus’s (HPV) role in pterygium pathogenesis, its autoinoculation from genitalia to ocular surface, potential cytokines involved, and crosstalk cytokines between pterygium and dry eye (DE). This cross-sectional study enrolled 25 healthy controls (HCs) and 116 pterygium patients. Four subgroups of pterygium and DE were used in cytokine evaluations. Conjunctival and pterygium swabs and first-void urine samples (i.e., genitalia samples) were collected for HPV DNA detection using real-time polymerase chain reaction. Tear cytokines interleukin (IL)-6, IL-18, and vascular endothelial growth factor (VEGF) in tears were evaluated. No HPV DNA was detected in conjunctival or pterygium swabs. No association was found between HPV DNA in urine samples and that from conjunctival or pterygium swabs. Tear VEGF levels were significantly higher in pterygium patients than in HCs, with no markedly different levels between primary and recurrent pterygia. Tear IL-6, IL-18, and tear VEGF were significantly higher in participants with DE, regardless of pterygium status. In conclusion, HPV infection was not a pathogenic factor of pterygia. The hypothesis of HPV transmitting from the genitals to ocular surfaces was nullified. Tear VEGF was involved in both pterygia and DE, whereas tear IL-6 and IL-18 played roles only in DE.